Energy and Climate Policy: USA Continues to Trail behind, Despite Positive Change - Wolf-Peter Schill; Jochen Diekmann; Claudia Kemfert (Weekly Report, 2010)
In the course of current climate negotiations, the world is watching the United States in particular. Together with China, the U.S. is by far the largest emitter of greenhouse gases. Real progress in protecting the global climate requires substantial action on America's part. The U.S. has the potential to significantly reduce emissions. Per capita energy consumption in the U.S. is still about twice that of Europe. An assessment of current energy and climate policies in America is disillusioning. So far, federal and state measures have had only limited success - both in terms of increasing energy efficiency and in the use of renewable energy. While some regional initiatives are promising - for example, the establishment of renewable portfolio standards, or emissions trading schemes in the Northeast and West of the country - they ultimately lack sufficient ambition and scope. Proposals currently under debate in Congress for a national energy and climate protection law are highly contested, even though they do not set particularly demanding goals for reducing emissions in the medium term. Against this backdrop, the U.S. cannot be expected to catch up anytime soon in the area of climate protection.
Keywords: Q40; Q48; Q52; Q54; 330; Climate Policy; Energy Policy; Renewable Energy; USA